T-Cell Specificity Influences Disease Heterogeneity in Multiple Sclerosis. Issue 6 (17th November 2021) - Cruciani, Carolina; Puthenparampil, Marco; Tomas-Ojer, Paula; Jelcic, Ivan; Docampo, Maria Jose; Planas, Raquel; Manogaran, Praveena; Opfer, Roland; Wicki, Carla; Reindl, Markus; Jelcic, Ilijas; Lutterotti, Andreas; et al.
Abstract : Background and Objectives: Encouraged by the enormous progress that the identification of specific autoantigens added to the understanding of neurologic autoimmune diseases, we undertook here an in-depth study of T-cell specificities in the autoimmune disease multiple sclerosis (MS), for which the spectrum of responsible autoantigens is not fully defined yet. The identification of target antigens in MS is crucial for therapeutic strategies aimed to induce antigen-specific tolerance. In addition, knowledge of relevant T-cell targets can improve our understanding of disease heterogeneity, a hallmark of MS that complicates clinical management. Methods: The proliferative response and interferon gamma (IFN-γ) release of CSF-infiltrating CD4 + T cells from patients with MS against several autoantigens was used to identify patients with different intrathecal T-cell specificities. Fresh CSF-infiltrating and paired circulating lymphocytes in these patients were characterized in depth by ex vivo immunophenotyping and transcriptome analysis of relevant T-cell subsets. Further examination of these patients included CSF markers of inflammation and neurodegeneration and a detailed characterization with respect to demographic, clinical, and MRI features. Results: By testing CSF-infiltrating CD4 + T cells from 105 patients with MS against seven long-known myelin and five recently described GDP-l -fucose synthase peptides, we identified GDP-l -fucose synthase and myelin oligodendrocyte glycoprotein (35-55) responder patients. Immunophenotyping of CSF and paired blood samples in these patients revealed a significant expansion of an effector memory (CCR7 − CD45RA − ) CD27 − Th1 CD4 + cell subset in GDP-l -fucose synthase responders. Subsequent transcriptome analysis of this subset demonstrated expression of Th1 and cytotoxicity-associated genes. Patients with different intrathecal T-cell specificities also differ regarding inflammation- and neurodegeneration-associated biomarkers, imaging findings, expression of HLA class II alleles, and seasonal distribution of the time of the lumbar puncture. Discussion: Our observations reveal an association between autoantigen reactivity and features of disease heterogeneity that strongly supports an important role of T-cell specificity in MS pathogenesis. These data have the potential to improve patient classification in clinical practice and to guide the development of antigen-specific tolerization strategies.